How many doses and what type of antibiotic should be used as systemic antibiotic prophylaxis in primary hip and knee arthroplasty? A register-based study on 301,204 primary total and hemi- hip and total knee arthroplasties in Norway 2005–2023 - Olav Lutro; Marianne Bollestad Tjørhom; Tesfaye Hordofa Leta; Jan-Erik Gjertsen; Geir Hallan; Trond Bruun; Marianne Westberg; Tina Strømdal Wik; Christian Thomas Pollmann; Stein Håkon Lygre; Ove Furnes; Lars Engesæter; et al. (Acta Orthopaedica)
Background and purpose: Guidelines for systemic antibiotic prophylaxis (SAP) in arthroplasty surgery vary worldwide from repeated doses to only 1 preoperatively. We aimed to investigate, primarily whether 4 doses reduced the risk of PJI compared with 1 to 3 doses, and secondarily if there was a difference between types of antibiotics. Methods: Patients reported to the Norwegian Arthroplasty Register and the Norwegian Hip Fracture Register with primary total knee (TKA), total (THA) or hemi- (HA) hip arthroplasty between 2005 and 2023 were included. Cases with 1 to 4 doses of cefalotin (half-life = 45 minutes), cefazolin (90 minutes), cefuroxime (70 minutes), cloxacillin (30 minutes), or clindamycin (180 minutes) were assessed. Primary outcome was 1-year risk of reoperation (adjusted hazard rate ratio; aHRR) for PJI and was estimated by Cox regression analyses. Secondary outcomes were reoperation for PJI and reoperation for any cause with follow-up of up to 19 years. Non-inferiority analyses and propensity score matching with subsequent Kaplan–Meier analyses were performed with a predetermined non-inferiority margin of 15% (aHRR = 1.15). Results: 301,204 cases were included. Of these, 3,388 (1.1%) were reoperated on for PJI within 1 year. The 1-year incidence of reoperation for PJI was 98/9,760 (1.0%) for 1 dose of SAP, 109/10,956 (0.9%) for 2 doses, 178/18,948 (0.9 %) for 3 doses, and 3,003/261,540 (1.0%) for 4 doses. The 1-year risk (aHRR, 95% confidence interval [CI]) of reoperation for PJI was 1.0 (CI 0.8–1.2), 0.9 (CI 0.8–1.2), and 0.9 (CI 0.9–1.1) for 1, 2, and 3 doses, respectively, compared with 4 doses. The 1-year incidence of reoperation for PJI was 2,162/183,964 (1.2%) for cefalotin, 993/91,159 (1.1%) for cefazolin, 35/4,435 (0.8%) for cefuroxime, 85/9,022 (0.9%) for cloxacillin, and 113/12,624 (0.9%) for clindamycin. Compared with cefazolin, cloxacillin (1.2, CI 1.0–1.6) and cefalotin (1.4, CI 1.2–1.5) had a higher risk of reoperation for PJI, whereas cefuroxime (1.0, CI 0.7–1.4) and clindamycin (1.1, CI 0.9–1.3) had a similar risk. Conclusion: 4 doses of SAP did not reduce the risk of PJI compared with 1 to 3 doses in primary arthroplasty as measured against PJI. Cefazolin, the 1st-generation cephalosporin with the longest half-life, showed the lowest risk of PJI.